The Design and Development of Parent-Children Vaccination Alert System - Bukohwo Michael Esiefarienrhe; Mmamosweu Caroline Patricia Makokoe (Universitas Bina Darma, 2023)
Elevated rates of child mortality in many developing contries can be attributed to a complex interplay of poverty, malnutrition, and a host of preventable and non-preventable diseases. While vaccines for many of these diseases have been widely disseminated in developed countries through efforts from organizations such as WHO, UNICEF, and the Bill & Melinda Gates Foundation, adherence to vaccination schedules remains suboptimal in less affluent nations. This shortfall is largely due to the challenges parents and guardians face in scheduling and maintaining vaccine appointments for their children. To address this gap, our study employed the Design Science Research Process (DSRP) model to develop an integrated booking and SMS reminder system aimed at simplifying the immunization process. The application was engineered using Object-Oriented Agile methodologies and incorporates a prototype for client testing and early-stage implementation. As immunization stands as a cornerstone for managing vaccine-preventable diseases, this system offers a crucial solution to enhance child healthcare. It not only aids in reducing mortality rates but also simplifies the documentation and archival of vaccination records, thereby improving their accessibility. This system introduces an innovative approach that allows parents to book their child’s vaccination appointments online, thereby eliminating the need for physical presence at healthcare facilities. The implementation of this system is expected to alleviate congestion in clinics and hospitals, streamlining the vaccination process and potentially improving overall public health.